The Cambridge encyclopedia of the English language - Crystal, David 1941- (Cambridge University Press, 1995)
An exploration of the history, structure, and use of the English language discusses its origins and evolution, its use in literature, and its structural features, and addresses grammar, pronunciation, and vocabulary